1994
DOI: 10.1007/bf01627591
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the study of the tributaries and the termination of the external jugular vein

Abstract: The dissection of 100 external jugular veins in 50 cadavers was the object of this anatomic study. A certain number of notions concerning the afferent veins, the mode of termination and the valvular system of this vessel were defined. 1) Afferent veins. Along its pathway toward the deep venous system, the external jugular vein successively received: the transverse cervical vein in 88 cases (88%), usually opposite the intersection of the external jugular vein with the dorsal border of the sterno- cleidomastoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 3 publications
0
39
0
Order By: Relevance
“…The AJV opens into the EJV (as reported by Deslaugiers et al, 1994) in 46% and into the SCV in 54% of the cases. Its diameter is usually inverse to that of the EJV (Standring et al.).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The AJV opens into the EJV (as reported by Deslaugiers et al, 1994) in 46% and into the SCV in 54% of the cases. Its diameter is usually inverse to that of the EJV (Standring et al.).…”
Section: Resultsmentioning
confidence: 81%
“…1259 has even the double diameter (Standring et al, 2008). The EJV has been found to flow in the jugulo-subclavian junction in the anatomical study of Deslaugiers et al (1994) on 50 cadavers in 60%, either directly in 8% or after having formed a common trunk, most often formed on the right, with the TCV in 52%. The termination of the EJV in the jugulosubclavian junction has also been noted by Sobbota as well as by Bouchet & Guilleret (Deslaugiers et al).…”
mentioning
confidence: 99%
“…2,6 In a study conducted on 50 adult cadavers in 1994, external jugular vein in 60% of the cases was reported to end in venous angle; in 36% of them, it was stated to end in subclavian vein, and in 4% of them, it was said to end in internal jugular vein. 9 In another study conducted in 1996, it is stated that external jugular vein ends in venous angle at a rate of 72%, while it ends in subclavian with 26% and ends in internal jugular with 2%. 10 The researchers identified different variations also for cephalic vein, which is the longest superficial vein of the upper extremity.…”
Section: Discussionmentioning
confidence: 98%
“…Deslaugiers et al (28) reported that the EJV usually enters into the jugulo-subclavian venous confluence (type A, 60%), into the SCV at a distance from its junction with the IJV (type B, 36%) or into the trunk of the IJV (type C, 4%) (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%